2020
DOI: 10.1177/0146167220921065
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Transgender Attitudes Independently Predict Beliefs About Gender and Transgender People

Abstract: Surprisingly little is known about transgender attitudes, partly due to a need for improved measures of beliefs about transgender people. Four studies introduce a novel Implicit Association Test (IAT) assessing implicit attitudes toward transgender people. Study 1 ( N = 294) found significant implicit and explicit preferences for cisgender over transgender people, both of which correlated with transphobia and transgender-related policy support. Study 2 ( N = 1,094) found that implicit transgender atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 56 publications
2
38
1
Order By: Relevance
“…In the US, individual differences in gender essentialism predict sexism (Lee et al, 2020;Smiler & Gelman, 2008), acceptance of existing gender disparities (Lee et al, 2020), association of gender norms with the self (Coleman & Hong, 2008;Smiler & Gelman, 2008), preference for traditionally gendered others (Swigger & Meyer, 2019;Tinsley et al, 2015), and transprejudice (Axt et al, 2021;Norton & Herek, 2013;Prusaczyk & Hodson, 2020;Rad et al, 2019;Tee & Hegarty, 2006;Wilton et al, 2019). As such, these beliefs may play a noteworthy role in moderating how people ascribe stereotypes to transgender groups.…”
Section: Ontological Beliefs Guiding Gender Stereotypesmentioning
confidence: 99%
“…In the US, individual differences in gender essentialism predict sexism (Lee et al, 2020;Smiler & Gelman, 2008), acceptance of existing gender disparities (Lee et al, 2020), association of gender norms with the self (Coleman & Hong, 2008;Smiler & Gelman, 2008), preference for traditionally gendered others (Swigger & Meyer, 2019;Tinsley et al, 2015), and transprejudice (Axt et al, 2021;Norton & Herek, 2013;Prusaczyk & Hodson, 2020;Rad et al, 2019;Tee & Hegarty, 2006;Wilton et al, 2019). As such, these beliefs may play a noteworthy role in moderating how people ascribe stereotypes to transgender groups.…”
Section: Ontological Beliefs Guiding Gender Stereotypesmentioning
confidence: 99%
“…It may be important to consider these findings in light of the temporal context in which the research took place. For instance, societal attitudes regarding the distinction between sex and gender and the recognition of nonbinary sex and gender identities have only somewhat recently been a part of public discourse and have shifted drastically over time (Axt et al, 2021; Brown et al, 2018), including over the time period represented by articles in the present review. However, it is also important to note that diverse sex/gender groups are not a new phenomenon in their existence.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that negative implicit evaluation is related to more negative, non-deliberate social behavior, such as aggressive behaviors in social interactions with peers (Lansu, 2018), and nonverbal communication (Dovidio et al, 2002). In addition, a recent study indicated that compared to explicit attitudes, implicit transgender attitudes predict beliefs and experiences, including gender essentialism, contact with transgender people, and support for transgender-related policies (Axt et al, 2020). Our findings partially confirmed the hypothesis that implicit information preference mediates the influence of regulatory focus on (not explicit) information choice behavior.…”
Section: Discussionmentioning
confidence: 99%